Young star clusters and the structure of the second Galactic quadrant II. Issue 2 (25th June 2019) - Molina Lera, J A; Baume, G; Gamen, R
ABSTRACT: Galactic spiral arms are traced using young objects as giant molecular clouds, H ii regions, OB stars, or young open/embedded clusters. To improve the knowledge of the Galactic structure in the second quadrant we selected, from more than 200 open clusters covered by the SDSS, a sample of 10 young stellar clusters to conduct a spectrophotometric study. Photometric data were provided by SDSS and APASS in the optic bands and by 2MASS and WISE in the infrared. Spectroscopic information was obtained from observations acquired with GMOS/GEMINI complemented with data from the literature. For six of the 10 clusters, distances were also obtained with our astrometric Gaia data analysis. To perform all tasks we used a suite of tools developed by us. Our results show that these open clusters are distributed along three spiral arms, covering distances from 1.8 to 8.0 kpc. We confirm, using our novel spectroscopic data, our previews photometric estimations regarding the Galactic location of the cluster Teutsch 45. We found that it is located beyond the 'Outer Arm' and probably belong to the more distant 'New Arm' extending its trace almost to the anticentre. Hence, it was possible to get a better picture of the structure of the outer regions of the Galaxy. For clusters with pre-main-sequence populations we also found traces of coeval star formation processes. Regarding spectroscopic data and most massive members of the clusters, we discovered seven B-type stars, all earlier than B4 and we also confirmed the spectral classification of one O8-8.5 type star.